Knockout of Nur77 Leads to Amino Acid, Lipid, and Glucose Metabolism Disorders in Zebrafish - Xu, Yang; Tian, Juanjuan; Kang, Qi; Yuan, Hang; Liu, Chengdong; Li, Zhehui; Liu, Jie; Li, Mingyu (Frontiers in Endocrinology, 2022)
Orphan nuclear receptor Nur77 has been reported to be implicated in a diverse range of metabolic processes, including carbohydrate metabolism and lipid metabolism. However, the detailed mechanism of Nur77 in the regulation of metabolic pathway still need to be further investigated. In this study, we created a global Nur77 knockout zebrafish model by CRISPR/Cas9 technique, and then performed the whole-organism RNA sequencing analysis in wild type and nur77-deficient zebrafish to dissect the changes genes in metabolic-related pathways. We found that many genes involved in amino acid, lipid, and carbohydrate metabolism were changed more than two-fold. Furtherly, we revealed that nur77-/- mutant displayed increased total cholesterol (TC) and triglyceride (TG), alteration in total amino acids, as well as elevated glucose. We also demonstrated that the elevated glucose was not due to the change of glucose uptake, but was likely caused by the disorder of glycolysis/gluconeogenesis and the impaired β cell function, including down-regulated of insb expression, reduced β-cell mass, and suppressed insulin secretion. Importantly, we also verified that targeted expression of Nur77 in the β cells is sufficient to rescue the β-cell defects in global nur77-/- larvae zebrafish. These results provide new information about the global metabolic network that Nur77 signaling regulates, as well as the role of Nur77 in β cell function.